Development of Indonesian Original Medicine: A Study of Nodiar Phytopharmaceutical Products as Traditional Medicine - Rohama, Rohama; Nabila, Putri; Witin, Rafelita Septania B.; Ismiadi, Rahmad; Rahmawati, Rahmawati; Kusnia, Risha I. K. (Universitas Ibn Khaldun Bogor, 2024)
The development of traditional Indonesian medicine is important in the context of sustainable public health. Nodiar, a phytopharmaceutical that relies on local natural ingredients, is attracting attention as a potential effective and safe drug. This article combines the results of a literature review related to Nodiar in the context of traditional medicine in Indonesia. This review includes an evaluation of chemical composition, pharmacological activity, clinical trials, as well as regulatory aspects and development standards. It is hoped that the results of this study can make a positive contribution to the development and utilization of Nodiar as one of the potential indigenous medicines in Indonesia.